Morphological study of a connexin 43‐GFP reporter mouse highlights glial heterogeneity, amacrine cells, and olfactory ensheathing cells. Issue 11 (30th March 2017) - Theofilas, Panos; Steinhäuser, Christian; Theis, Martin; Derouiche, Amin
Abstract : Connexin 43 (Cx43) is the main astrocytic connexin and forms the basis of the glial syncytium. The morphology of connexin‐expressing cells can be best studied in transgenic mouse lines expressing cytoplasmic fluorescent reporters, since immunolabeling the plaques can obscure the shapes of the individual cells. The Cx43kiECFP mouse generated by Degen et al. (FASEBJ 26:4576, 2012) expresses cytosolic ECFP and has previously been used to establish that Cx43 may not be expressed by all astrocytes within a population, and this can vary in a region‐dependent way. To establish this mouse line as a tool for future astrocyte and connexin research, we sought to consolidate reporter authenticity, studying cell types and within‐region population heterogeneity. Applying anti‐GFP, all cell types related to astroglia were positive—namely, protoplasmic astrocytes in the hippocampus, cortex, thalamus, spinal cord, olfactory bulb, cerebellum with Bergmann glia and astrocytes also in the molecular layer, and retinal Müller cells and astrocytes. Labeled cell types further comprise white matter astrocytes, olfactory ensheathing cells, radial glia‐like stem cells, retinal pigment epithelium cells, ependymal cells, and meningeal cells. We furthermore describe a retinal Cx43‐expressing amacrine cell morphologically reminiscent of ON‐OFF wide‐field amacrine cells, representing the first example of a mammalian CNS neuron‐expressing Cx43 protein. In double staining with cell type–specific markers (GFAP, S100ß, glutamine synthetase), Cx43 reporter expression in the hippocampus and cortex was restricted to GFAP + astrocytes. Altogether, this mouse line is a highly reliable tool for studies of Cx43‐expressing CNS cells and astroglial cell morphology. © 2017 Wiley Periodicals, Inc.